Adsorption of sulfone compounds produced in the oxidative desulfurization process using activated clay - Sapitan, Jhomee Fe F. (College of Engineering, University of the Philippines Diliman, 2014)
More stringent environmental standard and negative impacts to human and environment demands a continuous search for the most efficient and least expensive sulfur removal process in diesel. In the Philippines, the law mandates reduction in sulfur content of diesel to less than 50 ppm by 2016. In this paper, a sulfur removal technique was investigated by employing oxidation and adsorption. Simulating hydrogen peroxide as oxidant together with phosphotungstic acid as catalyst and tetraoctylammonium bromide as phase transfer agent, sulfur-containing compounds in diesel were successfully converted to their sulfone form. Using activated clay, the sulfone forms of sulfur-containing compounds in diesel were satisfactorily reduced resulting to less than 10 ppm S, achieving the EU Euro IV standard, This study investigated the effects of selected parameters in removing sulfur in diesel. Based from the batch experiment results, increasing adsorbent mass, agitation rate and temperature increases the rate of removal. The oxidation and adsorption process conducted successfully reduced the sulfur content of diesel from 110.9.3 to 6 ppm. Furthermore, kinetic study revealed that the rate-limiting mechanism is chemisorptions and the best-fit equilibrium correlation is Langmuir isotherm over Freundlich and Dubunin-Radushkevick isotherms. In addition, the thermodynamic paramaters (ΔG0 ΔH0 and ΔS0) showed that the adsorption process was spontaneous, favourable and endothermic in nature. The results described above confirmed the applicability of activated clay in the removal of sulfur in diesel.